FAKTOR RISIKO KEJADIAN SKABIES DI WILAYAH PUSKESMAS OLAK KEMANG KOTA JAMBI - Suparmi Suparmi; Supriatna Supriatna (Universitas Batanghari Jambi, 2015)
Background: Scabiesis a contagious disease, initial observation indicates that patients with scabies are foundin Olak Kemang Health Center Area, Jambi City. Scabies in human could be affected by human factors, environmental and health servicesObjective : This study aimed to identify risk factor related to scabies incidence at Olak Kemang Health Center Area, Jambi CityMethod: This research was an analytic observational study, using a case-control study design. The variable measured wereage, education level, economic status, knowledge, personal hygiene, contact history with scabies patients, humidity and occupancy density. The study population were people that live in Olak Kemang area. There were 44 case sample in this study. As a control group, there were 44 people that is not asufferer of scabies in Olak Kemang Area taken randomly. Data were collected by questionnaire and processed by univariable analysis, bivariable analysis using Chi-square statistic test and multivariable analysis with logistic regression.Result : Research results showed that there was significant relationship as a risk factor between scabies incidence and age, education level, economic status, knowledge, personal hygiene, contact history with scabies patient and occupancy density. There was no relationship between scabies incidence and room humidity factor.Conclusion :There was are lationship between age, education level, economic status, knowledge, personal hygiene, contact history with scabies patient and occupancy density of scabies incident. There was no relationship between the incidence of scabies and room humidity factor.Keywords: Risk Factor, Scabies